Generalization of the jump postulate and Brayton‐Moser's mixed potential for the analysis of RTD circuits. (4th March 2015) - Thiessen, Tina; Popp, Michael; Zorn, Christoph; Mathis, Wolfgang
Summary: In this paper, the series connection of resonant tunneling diodes (RTDs) will be analyzed with respect to their stability properties. An alternative approach to the commonly used loadline construction for the analysis of circuits utilizing the series connection of RTDs is presented. Furthermore, the basins of attraction of multiple operating points will be determined analytically by Brayton‐Moser's mixed potential function . Therewith, the jump postulate by Andronov et al. will be generalized for series connected N‐type nonlinearities. In addition, the numerical results will be verified by measurements. At the end, the discussed method is applied to the monostable‐bistable transition logic element, which today is one of the most promising logic circuits in nanoelectronics. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A new systematic method for analyzing circuits with series connected resonant tunneling diodes is presented. Therewith, not only all direct current operating points will be determined but also the basins of attraction will be calculated analytically. Furthermore, the jump postulate by Andronov et al. will be generalized for series connected N‐type nonlinearities. With the proposed method, the complex dynamics of a monostable and bistable transition logic element will be illustrated and parasitic output voltage spikes will be explained.